2014
DOI: 10.1039/c3ce41763h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally controlled ZnO nanosheet self-assembled hollow spheres/hierarchical aggregates and their photocatalytic activities

Abstract: We synthesized ZnO nano-micro structures, including microrods, nanosheets, a nanosheet selfassembled hollow sphere (NSHS), and a hollow hierarchical aggregate (HHA) by changing the concentration of trisodium citrate in a hydrothermal process. The NSHS was formed by the self-assembly of 2D nanosheets on the surface of a formaldehyde bubble, while the HHA was obtained by the self-assembly and hierarchical arrangement of NSHS. The photocatalytic activities of the ZnO structures were evaluated from the degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…In the hydrothermal process, zinc nitrate acts as a Zn 2þ precursor and hexamethylenetetramine reacts with water to produce hydroxide anion (OH À ) under reflux at 95 C. Zn 2þ reacts with OH À to produce ZnO nanostructure [25]. The reactions involved in the synthesis of ZnO as follows:…”
Section: Resultsmentioning
confidence: 99%
“…In the hydrothermal process, zinc nitrate acts as a Zn 2þ precursor and hexamethylenetetramine reacts with water to produce hydroxide anion (OH À ) under reflux at 95 C. Zn 2þ reacts with OH À to produce ZnO nanostructure [25]. The reactions involved in the synthesis of ZnO as follows:…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35] Many previous studies have been conducted to enhance the photocatalytic activity of ZnO using different morphologies, including nanoparticles, nanotubes, and hollow spheres. [36][37][38][39] The basic strategies for improving the photocatalytic activity of ZnO are extending the light response range and inhibiting the photoexcited charge carrier recombination. Although metal suldes (M x S) have been extensively used as photocatalysts, until recently they have not been employed in photocatalytic composites.…”
mentioning
confidence: 99%
“…These ZnONP interacted with hydroxyl groups of amylopectin and trapped in the branched structure of amylopectin [17]. Khoa et al also reported the hollow spheres of ZnOassembled (wrapped with Au/grapheme) and self- assembled ZnO nanosheet with photocatalytic potential [18,19].…”
Section: Electron Microscopy Analysismentioning
confidence: 95%